USING LEARNING JOURNAL TECHNIQUE TO IMPROVE THE RECOUNT TEXT WRITING SKILL OF THE TENTH GRADERS OF MAN 1 KOTA MAGELANG IN THE ACADEMIC YEAR 2017/2018 - Firda Khoirun Nisa' (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2018)
Based on the syllabus of 2013 Curriculum, students of the tenth graders of senior high school should be able to produce some kinds of text. In relation to the recount text, students of the tenth graders (X Agama 2) of MAN 1 Kota Magelang still had difficulty in making good recount text. The average score of the students was 54. This score is less than the minimum standard of the score which is 70. The objectives of this research is to know whether the use of Learning Journal technique can improve the students’ motivation in learning the recount text writing skill of the tenth graders of MAN 1 Kota Magelang in the academic year 2017/2018.  The writer conducted a classroom action research that was divided into Pre Cycle, Cycle I, and Cycle II. In collecting the data, the writer used non-test technique (observation and questionnaire) to know the improvement of the students’ motivation in learning writing of the recount text and test technique to know the improvement of the recount text writing skill of the students. There were 26 students of X Agama 2 of MAN 1 Kota Magelang as the subject of the research. As the result, there was an improvement of students’ motivation to learn English after the writer used Learning Journal technique. Furthermore, the students’ motivation in Pre-Cycle was 54.44. However the motivation improved to be 73.37 after they were taught by using Learning Journal technique in Cycle I. Then it continued to improve in Cycle II and the motivation improved to be 88.46. Keyword - Recount text, Learning Journal technique, Writing Skill.